ANALISIS IMPLEMENTASI KECAKAPAN HIDUP MELALUI PROGRAM IMTAQ SISWA KELAS III B SD ISLAM AL MADINA - Ilma Ludvitasari; Ngurah Ayu Nyoman Murniati; Sukamto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The aims of this study was to determine the implementation of life skills that are oriented towards the IMTAQ program for third grade students at SD Islam Al Madina Semarang. The type of research used is descriptive qualitative research which obtains data from interviews, observations, and documentation. The data that has been collected is processed using a triangulation technique and explained using a descriptive method written according to the source of the data obtained in the field. The results of this study indicate that the application of IMTAQ-oriented student life skills implemented at Al Madina Islamic Elementary School has been carried out according to very good habits, with an average score of 91%. So it can be concluded that the implementation of life skills for class III B students at SD Islam Al Madina is running with a high percentage of very good categories.